Pathology-MRI Correlation of Hepatocarcinogenesis: Recent Update - Jimi Huh; Kyung Won Kim; Jihun Kim; Eunsil Yu (Korean Society of Pathologists & the Korean Society for Cytopathology, 2015)
Understanding the important alterations during hepatocarcinogenesis as well as the characteristic magnetic resonance imaging (MRI) and histopathological features will be helpful for managing patients with chronic liver disease and hepatocellular carcinoma. Recent advances in MRI techniques, such as fat/iron quantification, diffusion-weighted images, and gadoxetic acid-enhanced MRI, have greatly enhanced our understanding of hepatocarcinogenesis.